Nutritional energy and protein requirements improvement of in situ incubation methods in goats and sheep. - Santos, Antonio Carneiro Santana dos (2021)
Then, the objective of this study was to determine the nutritional requirements of energy and protein in goats and sheep, under tropical condition, and to compare the dietary requirement estimates between these species. A total of 34 male goats and 34 male sheep were used, with an initial average body weight (BW) of 21 ± 3.9 kg, and age close to 110 days. The experiment lasted 109 days. The experiment was conducted in completely randomized design. After the end of the adaptation period, four animals of each specie were randomly chosen and slaughtered, in order to determine the empty body weight (EBW) and initial body chemical composition. After slaughter, these eight animals composed the group called reference, representing the initial body composition of the other animals that remained in the experiment. After that, another four animals of each specie were randomly designated to another group called maintenance. The remained 26 animals (13 goats and 13 sheep) were included in the group for ad libtum intake, and they were slaughtered at the end of the experiment together with the maintenance group. The comparative slaughter method was applied to evaluate the nutrient requirements. There was difference (P < 0.05) between species for all intake variables (kg/d and g/kg of BW), but this effect was not observed (P>0.05) for digestibility of the nutrients evaluated. There was greater (P < 0.01) microbial CP synthesis in sheep compared to goats (Table 6). However, the microbial efficiency expressed in g/kg of digestible OM (P = 0.23) and g/kg of TDN (P = 0.24) did not differ between species. The NEm was 0.0683 Mcal/EBW0.75/day.22 The requirement of metabolizable energy for maintenance (MEm) was 0.115 Mcal/kg EBW0.75/day, and the km was 0.599, for both species. The estimated NEg for uncastrated male dorper goats was 0.545 Mcal/day, considering a body weight of 30 kg and ADG of 200 g/day, while the estimated NEg for uncastrated lambs with the same body weight and ADG was 0.585 Mcal/day. The kg obtained was 0.113 and 0.699 for goats and sheep respectively. The NPm was 0.318 g/kg EBW0.75/day. The k that allows to convert NPg in MPg was represented by β1= 0.09794, which was obtained from the equation to estimate NPm. Similarity is observed in the energy requirement for maintenance in goats and sheep. However, species show differences in energy requirements for gain and efficiency of energy use for gain.